History of the Bait Al-Hikmah Library During the Golden Age of Bani Abbasiyah - Jeni Susana; Tri Agus Yani (Jurnal El-Pustaka, 2024)
Bait al-hikmah is a silent evidence of the progress of civilization that occurred during the Abbasid dynasty, the advancement of science made Bait al-hikmah the direction of information in its time. This study aims to find out about the History of the Bait Al Hikmah Library During the Golden Age of the Abbasids. This research method uses library research with a qualitative approach. Researchers obtain information through books, articles and journals related to the research topic. The focus of this study is the Bait Al-Hikmah Library During the Golden Age of the Abbasids. In history, the background to the establishment of Bait al-Hikmah is due to internal factors from the belief in the value of religious teachings that always encourage its adherents to learn and seek knowledge. During the Abbasid Dynasty which adhered to the Mu'tazilah ideology, the ruling caliphs loved science and encouraged the development ofscience at that time. In addition, the conditions at that time were very conducive to transferring Greek and Persian treasures into the arms of Muslims. In addition, the rulers around the time before the founding of the House of Wisdom were people who loved knowledge.